Neovascularization of hepatocellular carcinoma in a nude mouse orthotopic liver cancer model: a morphological study using X-ray in-line phase-contrast imaging. Issue 1 (December 2017) - Li, Beilei; Zhang, Yiqiu; Wu, Weizhong; Du, Guohao; Cai, Liang; Shi, Hongcheng; Chen, Shaoliang
Abstract Background This study aimed to determine whether synchrotron radiation (SR)-based X-ray in-line phase-contrast imaging (IL-PCI) can be used to investigate the morphological characteristics of tumor neovascularization in a liver xenograft animal model. Methods A human hepatocellular carcinoma HCCLM3 xenograft model was established in nude mice. Xenografts were sampled each week for 4 weeks and fixed to analyze tissue characteristics and neovascularization using SR-based X-ray in-line phase contrast computed tomography (IL-XPCT) without any contrast agent. Results The effect of the energy level and object–to-detector distance on phase-contrast difference was in good agreement with the theory of IL-PCI. Boundaries between the tumor and adjacent normal tissues at week 1 were clearly observed in two-dimensional phase contrast projection imaging. A quantitative contrast difference was observed from weeks 1 to 4. Moreover, 3D image reconstruction of hepatocellular carcinoma (HCC) samples showed blood vessels inside the tumor were abnormal. The smallest blood vessels measured approximately 20 μm in diameter. The tumor vascular density initially increased and then decreased gradually over time. The maximum tumor vascular density was 4.29% at week 2. Conclusion IL-XPCT successfully acquired images of neovascularization in HCC xenografts in nude mice.